Study of WiMAX simulation - Ahmed Al Amin; Khan, Moniruzzaman; Alam, Saiful; Mony, Riaz Mohammad (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.